Design, testing, and FEM simulation of interlaced fiber composite structures - GENÇ, GARİP (ELSEVIER SCI LTD, 2009)
Design, testing, and FEM simulation of FRP structural parts manufactured using continuous fiber and light-curing resin are presented in this study. The structures can be described as formed by girders spaced by skew ribs. The study was limited to plane structures with two girders and 45 ribs between girders. Roving was positioned along the girders and the ribs so that fibers were interlaced at the joints between the ribs and girders. Several deposition paths were designed. They differ by interlacing, and proportions of fiber in the girders and ribs. Overall stiffness and strength of the structures were investigated in bending, and local deformations were measured with the strain gauges. Finite element modeling of four-point bending test for some test pieces were carried out using commercial code ANSYS to predict the deflection and the strains. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Strength; Finite element analysis (FEA); Mechanical testing; Joints; BEHAVIOR